2006
DOI: 10.1002/ajmg.b.30252
|View full text |Cite
|
Sign up to set email alerts
|

Suggestive evidence for association of the circadian genes PERIOD3 and ARNTL with bipolar disorder

Abstract: Bipolar affective disorder (BPAD) is suspected to arise in part from malfunctions of the circadian system, a system that enables adaptation to a daily and seasonally cycling environment. Genetic variations altering functions of genes involved with the input to the circadian clock, in the molecular feedback loops constituting the circadian oscillatory mechanism itself, or in the regulatory output systems could influence BPAD as a result. Several human circadian system genes have been identified and localized re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
151
2
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(160 citation statements)
references
References 47 publications
5
151
2
2
Order By: Relevance
“…Haplotypes in BMAL1 and Per3 were found to significantly associate with BPD in one study (Nievergelt et al, 2006). Furthermore, a SNP in BMAL1 and a SNP in the Timeless gene have also been identified that associate with BPD (Mansour et al, 2006).…”
Section: Human Genetic Studiesmentioning
confidence: 96%
See 1 more Smart Citation
“…Haplotypes in BMAL1 and Per3 were found to significantly associate with BPD in one study (Nievergelt et al, 2006). Furthermore, a SNP in BMAL1 and a SNP in the Timeless gene have also been identified that associate with BPD (Mansour et al, 2006).…”
Section: Human Genetic Studiesmentioning
confidence: 96%
“…It should be noted that additional studies have found associations between members of the molecular clock and other psychiatric disorders such as schizophrenia and alcoholism, suggesting that these genes are important in a range of psychiatric conditions (Spanagel et al, 2005;Mansour et al, 2006). However, in general, most of these studies only find modest associations, and other studies that have examined SNPs throughout the sequence of some of the central members of the circadian clock have found no associations with these genes and any psychiatric disorders (Shiino et al, 2003;Nievergelt et al, 2005;Mansour et al, 2006;Nievergelt et al, 2006). Therefore the functional importance of these variations is still uncertain, and only certain members of the circadian clock may be involved.…”
Section: Human Genetic Studiesmentioning
confidence: 99%
“…Furthermore, suggestive evidence has recently been reported for the association of circadian gene variants including CLOCK, BMAL1, PER3 and TIMELESS with bipolar disorder. [31][32][33] Moreover, studies using pharmacogenomic animal models for bipolar disorder have revealed circadian genes as the candidate genes for mania and psychosis, which include BMAL1, GSK3b, CKId, CRY2 34 and DBP. 35 Despite the above-mentioned evidence implicating the circadian system in the pathophysiology of bipolar disorder, the functional and molecular basis of circadian anomalies in bipolar disorder has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, per3 knock out mice have only a slight decrease in the period of their circadian clock [51]. In humans, certain polymorphisms in the per3 gene and misregulation of per3 expression have been associated with breast cancer, chronic myeloid leukemia, bipolar disorder, and the structure of the sleep/wake cycle [15,41,58,61,62].…”
Section: The Pattern Of Exorh Transcription Is Controlled By a Combinmentioning
confidence: 99%